(untitled) (Medical Forum Monthly, 2022)
Objective: To determine association of papilledema with headache using 20D lens and a smartphone for fundoscopy. Study Design: Prospective Cross-sectional Study Place and Duration of Study: This study was conducted at the Ophthalmology OPD at Liaqat National Hospital, Karachi from, 25th May 2022 till 25th July 2022. Materials and Methods: Patients, presenting to ophthalmology OPD at Liaqat National Hospital, patient complaining of blurring of vision and difficulty focusing on distant object were included in our study. We used a 20D lens for indirect ophthalmoscopy and smartphone camera for recording and taking pictures. Participant’s pupils were dilated using 1% tropicamide drops and waited for 15-20 mins for pupil dilation. Video recording was done with flashlight switched on and recording was reviewed for fundus pictures and snap shots were taken from it. Results: 384 patients were included in the study. There were 65.6% male and 34.4% female patients in our study with mean age 41.93±13.50 years while majority (62.8%) were from age group >35 years. we found 3.6% of patients with obesity, 12.2% with diabetes mellitus, 14.3% with hypertension and 45.1% with headache and 7.3% of patients were found with papilledema. Strong association was found with papilledema and headache with p-value of <0.001. Conclusion: Strong association of papilledema with headache was found in patients who came with symptoms of blurry vision and We can reliably do fundus visualization with Smartphone based indirect ophthalmoscopy to view optic disc for presence of papilledema, can be cheap alternative to conventional ophthalmoscopy devices even in neurosurgical examinations, in covid-19 era where social distancing is a norm and proximity to the patients with direct ophthalmoscopy can be discomforting in these circumstances.